2016
DOI: 10.1039/c6ta04874a
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient electro-reduction of CO2 to formic acid by nano-copper

Abstract: Ultra-fine copper(ii) oxide nanoparticles were used for the electrocatalytic reduction of CO2 to formic acid at high Faradaic efficiencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(57 citation statements)
references
References 39 publications
2
51
1
Order By: Relevance
“…Moreover, additional confirmation of CuO state was seen with the broad satellite peaks at a higher binding energy than the main peaks. The main peak of Cu 2p 3/2 at 933.8 eV was accompanied by two satellite peaks on the higher binding energy side at about 943.8 eV and 941.5 eV, which suggests the existence of CuO [38][39][40][41]. From this figure, we can clearly see that the main peak of Cu 2p 1/2 at 953.8 eV and its satellite peak at 962.5 eV were separated by about 9.0 eV, which also confirms the presence of CuO [42].…”
Section: Catalyst Characterizationsmentioning
confidence: 94%
“…Moreover, additional confirmation of CuO state was seen with the broad satellite peaks at a higher binding energy than the main peaks. The main peak of Cu 2p 3/2 at 933.8 eV was accompanied by two satellite peaks on the higher binding energy side at about 943.8 eV and 941.5 eV, which suggests the existence of CuO [38][39][40][41]. From this figure, we can clearly see that the main peak of Cu 2p 1/2 at 953.8 eV and its satellite peak at 962.5 eV were separated by about 9.0 eV, which also confirms the presence of CuO [42].…”
Section: Catalyst Characterizationsmentioning
confidence: 94%
“…Cu(110) is the most active surface for the production of formate [optimized faradaic efficiency (FE) of 24.7 % at −0.80 V vs. RHE], whereas Cu(100) is the most inactive (FEHCOO- =9.0 % at −0.85 V vs. RHE). Recently, Darr and co‐workers reported that CuO‐derived Cu nanoparticles supported on a Nafion network could reduce CO 2 to formate at −1.4 V versus Ag/AgCl with a FE of 61 % and j HCOO- of approximately −2 mA cm −2 …”
Section: Introductionmentioning
confidence: 94%
“…Owing to the high market value and wide usage of formic acid, the development of facile methods for its production through the direct electrochemical reduction of CO 2 driven by renewable energy has become an irresistible proposition. In recent decades, various catalysts based on palladium, cobalt, tin, indium, lead, and metal‐free nitrogen‐doped carbon materials have been reported for this purpose (Table ) . The standard potential for the reduction of CO 2 to formic acid (CO 2 +2 H + +2 e − →HCOOH) is −0.20 V versus the reversible hydrogen electrode (RHE) .…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations